WORK-LIFE BALANCE AND JOB SATISFACTION ON EMPLOYEES’ PERFORMANCE AMONG WORKERS IN TERTIARY INSTITUTIONS - Roberts, Enyelunekpo; Afachung, Pius; Emmanuel, Sandra; Uye, Emmanuel (International Journal of Multidisciplinary Reseach, 2025)
Employees’ performance has been used as a standard of measurement in both private and public organizations. Studies on what would make employees’ to put in their best in their organizations have produced varying results. Therefore, this study was carried out to investigate work-life balance and job satisfaction as predictors of employees’ performance among workers in tertiary institutions in Rivers State, Nigeria. Cross-sectional survey design was utilized while purposive sampling technique was adopted to select the study populations. Data were collected from 280 participants using validated scales and analyzed using multiple regression to test one hypothesis which was accepted at p < .001 level of significance. The result demonstrated that work-life balance and job satisfaction jointly predicted employee performance among workers in tertiary institutions in Rivers State R2= .461, F(2, 277) = 105.803, p <.001. Furthermore, work-life balance (β = .466, p <.001) and job satisfaction (β = .370, p <.001) independently predicted employees’ performance among study participants. The study concludes that work-life balance and job satisfaction are robust predictors among study participants. It is recommended that these institutions should put in place enabling policies that would enhance good work-life balance and job satisfaction to improve workers’ performance.